Evolution of antibody landscape and viral envelope escape in an HIV-1 CRF02_AG infected patient with 4E10-like antibodies - Grupping Katrijn; Van Nieuwenhove Lies; Gray Elin; Willems Betty; Heyndrickx Leo; Dieltjens Tessa; Vanham Guido; Janssens Wouter (Retrovirology, 2009)
Abstract Background A minority of HIV-1 infected individuals develop broad cross-neutralizing (BCN) plasma antibodies that are capable of neutralizing a spectrum of virus variants belonging to different HIV-1 clades. The aim of this study was to identify the targeted epitopes of an individual with BCN plasma antibodies, referred to as ITM4, using peptide phage display. This study also aimed to use the selected mimotopes as tools to unravel the evolution of the antibody landscape and the viral envelope escape which may provide us with new insights for vaccine design. Results This study led us to identify ITM4 plasma antibodies directed to the 4E10 epitope located in the gp41 membrane-proximal external region (MPER). Analysis of antibody specificities revealed unusual immunogenic properties of the ITM4 viral envelope, as not only the V3 loop and the gp41 MPER but also the C1 and lentivirus lytic peptide 2 (LLP2) region seem to be targets of the immune system. The 4E10-like antibodies are consistently elicited during the 6-year follow up period. HIV-1 ITM4 pseudoviruses showed an increasing resistance over time to MPER monoclonal antibodies 4E10 and 2F5, although no changes are found in the critical positions of the epitope. Neutralization of COT6.15 (subtype C; 4E10-sensitive) pseudoviruses with alanine substitutions in the MPER region indicated an overlapping specificity of the 4E10 monoclonal antibody and the ITM4 follow up plasma. Moreover the 4E10-like antibodies of ITM4 contribute to the BCN capacity of the plasma. Conclusions Using ITM4 BCN plasma and peptide phage display technology, we have identified a patient with 4E10-like BCN antibodies. Our results indicate that the elicited 4E10-like antibodies play a role in virus neutralization. The viral RNA was isolated at different time points and the ITM4 envelope sequence analysis of both early (4E10-sensitive) and late (4E10-resistant) viruses suggest that other regions in the envelope, outside the MPER region, contribute to the accessibility and sensitivity of the 4E10 epitope. Including ITM4 specific HIV-1 Env properties in vaccine strategies may be a promising approach.